La pseudépigraphie comme procédé littéraire autonome: L'exemple des Pastorales - Burnet, Régis (Apocrypha, 2001)
It has been claimed that pseudepigraphy should be an innocent play on the author's name. Yet, a study of the Pastoral Epistles show that it is a genuine literary technique.Different enunciative strategies can be picked out and used either to put 1Tim and Tite together and to separate 2Tim; and to distinguish between two pseudepigraphical practices: actualization and anachronism.